Accuracy of Highly Sexually Active Gay and Bisexual Men's Predictions of Their Daily Likelihood of Anal Sex and Its Relevance for Intermittent Event-Driven HIV Pre-Exposure Prophylaxis. (1st April 2015) - Parsons, Jeffrey T.; Rendina, H. Jonathon; Grov, Christian; Ventuneac, Ana; Mustanski, Brian
Abstract : Objective: We sought to examine highly sexually active gay and bisexual men's accuracy in predicting their sexual behavior for the purposes of informing future research on intermittent event-driven HIV Pre-Exposure Prophylaxis. Design: For 30 days, 92 HIV-negative men completed a daily survey about their sexual behavior (n = 1688 days of data) and indicated their likelihood of having anal sex with a casual male partner next day. Method: We used multilevel modeling to analyze the association between self-reported likelihood of and subsequent engagement in anal sex. Results: We found a linear association between men's reported likelihood of anal sex with casual partners and the actual probability of engaging in sex, although men overestimated the likelihood of sex. Overall, we found that men were better at predicting when they would not have sex than when they would, particularly if any likelihood value greater than 0% was treated as indicative that sex might occur. We found no evidence that men's accuracy of prediction was affected by whether it was a weekend or whether they were using substances, although both did increase the probability of sex. Discussion: These results suggested that, men taking event-driven intermittent Pre-Exposure Prophylaxis, 14% of doses could have been safely skipped with a minimal rate of false negatives using guidelines of taking a dose unless there was no chance (ie, 0% likelihood) of sex on next day. This would result in savings of over US $1300 per year in medication costs per participant.